CO-PARENTING FACTORS THAT CONTRIBUTE TO ACADEMIC SUCCESS - Julia M. Bernard; David P. Nalbone; Lorna L. Hecker; Suzanne E. Degges-White (European Scientific Journal, ESJ, 2015)
This study assessed factors contributed from parents who live in two different households and that lead to academic success. Data were collected from undergraduates enrolled in a Midwestern satellite university. Academic success was defined by university enrollment, grade point average, and standardized testing scores. Co-parenting factors that were hypothesized to lead to academic success included the distance between parents homes (which further influenced time spent with the child, participation in child‘s activities, and participation in decision making) and financial stability (which also influenced participation in decision making and the level of conflict within the family). The original structural equation model revealed that the relationship linking the distance between homes and the time spent with the child was accurately described. Added to the model, after the Lagrange test, was a path from finances to participation in child‘s activities and time spent with the child. The financial stability of a family predicted the participation of the non-custodial parent in the child‘s activities, in the decision-making for the child, conflict, and the time spent with the child. Implications for practitioners who work with families with co-parenting responsibilities are discussed.